PENETAPAN BATAS DARAT INDONESIA – MALAYSIA DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (Studi Pada Peran Direktorat Topografi TNI AD Dalam Penetapan Batas Darat Indonesia - Malaysia Di Kecamatan Sei Menggaris Kabupaten Nunukan Provinsi Kalimantan Utara) - Hendri Susilo; Su Ritohardoyo; Ahmad Zubaidi (Universitas Negeri Medan, 2019)
This study discussed the determination of Indonesia-Malaysia land border and its implications for regional resilience (A Study of Roles of the Directorate of Topography of the Indonesian Army in the Determination of Indonesia-Malaysia Land Border in Sei Menggaris Nunukan North Kalimantan). The objectives of the study were (1) to study roles of the Directorate of Topography of the Indonesian Army in the determination of Indonesia-Malaysia land border, (2) to study the constraints faced and assessed the performance effectiveness of the Directorate of Topography of the Indonesian Army in the determination of Indonesia-Malaysia land border and (3)to trace the implication of Indonesia-Malaysia land border implemented by the Directorate of Topography of the Indonesian Army on regional resilience. This research applied the qualitative research method. Data collection methods were observations, in-depth interviews, documents and literatures review, and online data tracking.The findings indicated that roles of the Directorate of Topography of the Indonesian Army in the determination of Indonesia-Malaysia land border included border demarcation and Investigation, Refixation, and Maintenance (IRM) of Indonesia-Malaysia border. The determination of Indonesia-Malaysia land border strengthened the regional resilience of Sei Menggaris Nunukan North Kalimantan.Keywords: Land Border, Roles, Directorate of Topography of the Indonesian Army, Regional Resilience